Establishing a genetically engineered mouse ES cell line expressing an inducible Xist transgene along chromosome 19 - Tan, Christina En Hui (2018)
Xist (X-inactive specific transcript) RNA plays an important role in X chromosome inactivation (XCI), a dosage compensation mechanism mammalian females have evolved to transcriptionally silence one of two copies of X chromosomes they carry. Xist RNA remains in the nucleus, and during XCI onset, it is transcribed only from the future inactive X, coating the chromosome from which it is being produced. This results in the exclusion of RNA polymerase II and accumulation of epigenetic modifications, and eventually, silencing of the selected inactive X. Using RNA fluorescence in situ hybridisation (FISH), Xist RNA coating can be visualised as “clouds” within the cells. How Xist RNA propagates along the chromosome has been widely researched upon, yet the working mechanisms of Xist RNA still remain largely elusive. This project aims to address the question of whether Xist RNA is robust enough to recognise the boundaries of the chromosome from which it is being expressed from. This was achieved through establishing a genetically engineered cell line expressing an inducible Xist transgene along chromosome 19. As the smallest autosome in mice, occupying a much smaller area compared to the relatively large X, the stringency of the Xist RNA would be put to test, to recognise the smaller chromosome boundary of 19. We chose the Ainv15 cell line for this purpose as it contained a reverse tetracycline-controlled transactivator (rtTA) gene integrated into a constitutive locus, one of the components required to create a tractable, inducible system. A gene targeting site was inserted onto chromosome 19 via homology-directed repair (HDR) using the CRISPR-Cas9 genome editing method, and Cre-loxP mediated integration facilitated the insertion of the Xist transgene at the targeting site. The cell line established was verified by PCR genotyping, observation of colony fluorescence, and RNA FISH analysis. Further research with this model created can then be used to elucidate Xist cloud dynamics.